Trouble in zombie-town : an unofficial Minecrafter's adventure - Cheverton, Mark (Cheverton, Mark. Mystery of Herobrine, 2015)
"With his sister stuck in Minecraft, Gameknight999 will have to face a new enemy to save her!"--Back cover.